Optimizing early hip maturation strategies in neonatal hip immaturity and dysplasia: a cohort study and network meta-analysisResearch in context - Yu-Cheng Su; Ying-Yu Wang; Pei-Chun Lai; Yu-Kang Tu; Chih-Kai Hong; Ming-Tung Huang; Chii-Jeng Lin; Su-Ying Lee; Che-Wei Lin; Ching-Ju Fang; Po-Ting Wu; Fa-Chuan Kuan; et al. (EClinicalMedicine, 2025)
Summary: Background: Early intervention is crucial for optimizing hip maturation in developmental dysplasia of the hip (DDH). This study evaluates the clinical effectiveness of various conservative management approaches. Methods: We employed a dual-approach methodology combining original research with systematic evidence synthesis. First, we conducted a prospectively-designed retrospective cohort study from January 2021 to December 2023, comparing three treatment approaches in 103 hips: Pavlik harness (n = 35), double diapering (n = 39), and observation (n = 29), with 12-month follow-up. Second, we performed a network meta-analysis (NMA) registered in PROSPERO (CRD42024591239) to synthesize broader evidence on treatment effectiveness. We systematically searched MEDLINE, Embase, Scopus, Web of Science, and the Cochrane Central Register of Controlled Trials from inception to April 15, 2025, without language restrictions. The NMA included 9 studies (6 randomized, 3 non-randomized) encompassing 681 hips and compared five interventions: dynamic splinting (with/without sequential weaning), static splinting, observation, double diapering, and Mongolian swaddling. Primary outcomes were alpha angle improvement and normalization rates; secondary outcomes included treatment switching and adverse events. Findings: Pavlik harness showed superior one-month improvements in alpha angle (11.0° ± 5.1° versus 8.5° ± 2.9° versus 5.4° ± 4.5°, p < 0.0001) and femoral head coverage (0.149 ± 0.094 versus 0.081 ± 0.063 versus 0.053 ± 0.081, p < 0.0001) compared to double diapering and observation. The NMA revealed greater alpha angle improvements with dynamic splinting without weaning and double diapering versus observation [weighted mean difference (wMD): 3.34° (95% CI: 1.84–4.84, p < 0.0001) and 2.41° (0.72–4.10, p = 0.0052)]. Double diapering achieved higher normalization rates [weighted risk ratio (wRR): 1.47 (1.20–1.79, p = 0.0002)], while Mongolian swaddling increased failure risk [wRR: 0.65 (0.47–0.85, p = 0.0044)]. Dynamic splinting [wRR: 0.12 (0.04–0.38, p = 0.00022)] and dynamic splinting with sequential weaning [wRR: 0.05 (0.01–0.20, p < 0.0001)] reduced treatment switching rates. Adverse event rates were comparable across all interventions. Interpretation: Both dynamic splinting and double diapering effectively promote hip maturation in cases of hip immaturity (Graf IIa), with dynamic splinting producing more rapid improvements. For both immature and dysplastic hips (all Graf ≥ IIa), dynamic splinting appears to be the most effective treatment overall, while double diapering offers a viable alternative. Funding: This study was supported by grants from the National Science and Technology Council (NSTC 113-2314-B-006-090-, awarded to Chien-An Shih; NSTC 113-2314-B-006-085- and NSTC 113-2640-B-006-004-, awarded to Kai-Lan Hsu) and National Cheng Kung University Hospital (NCKUH-11404024, awarded to Chien-An Shih; NCKUH-11402044, awarded to Kai-Lan Hsu).